2011
DOI: 10.5194/nhess-11-1205-2011
|View full text |Cite
|
Sign up to set email alerts
|

Future storm surge impacts on insurable losses for the North Sea region

Abstract: Abstract. The influence of climate change on storm surges including increased mean sea level change and the associated insurable losses are assessed for the North Sea basin. In doing so, the newly developed approach couples a dynamical storm surge model with a loss model. The key element of the approach is the generation of a probabilistic storm surge event set. Together with parametrizations of the inland propagation and the coastal protection failure probability this enables the estimation of annual expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Other studies found indications of an increase in storm surge extremes at the North Sea coast associated with increased GHG concentrations (Woth et al, 2006;Langenberg et al, 1999). This is in line with Gaslikova et al (2011), who calculated an increase in insurable losses due to storm surges under future climate scenarios for this region. With respect to wave heights under scenario conditions, Grabemann and Weisse (2008) pointed at increasing extreme wave heights over large parts in the southern and eastern North Sea.…”
Section: Introductionsupporting
confidence: 75%
“…Other studies found indications of an increase in storm surge extremes at the North Sea coast associated with increased GHG concentrations (Woth et al, 2006;Langenberg et al, 1999). This is in line with Gaslikova et al (2011), who calculated an increase in insurable losses due to storm surges under future climate scenarios for this region. With respect to wave heights under scenario conditions, Grabemann and Weisse (2008) pointed at increasing extreme wave heights over large parts in the southern and eastern North Sea.…”
Section: Introductionsupporting
confidence: 75%
“…Pittock et al ., ; Reilly et al ., ; Webster ). Examples of probabilistic climate impact studies exist in several fields, including global crop yields (Tebaldi and Lobell, ), water resource management (New et al ., ; Manning et al ., ), and storm surges (Gaslikova et al ., ). A probabilistic flood risk study is that of Apel et al .…”
Section: Introductionmentioning
confidence: 82%
“…Pittock et al, 2001;Reilly et al, 2001;Webster 2003). Examples of probabilistic climate impact studies exist in several fields, including global crop yields (Tebaldi and Lobell, 2008), water resource management (New et al, 2007;Manning et al, 2009), and storm surges (Gaslikova et al, 2011). A probabilistic flood risk study is that of Apel et al (2006), in which a simple stochas-tic approach allowing a large number of simulations in a Monte Carlo framework provided the basis for a probabilistic risk assessment for an area of the Rhine (between Cologne and Rees, with a focus on the polder at Mehrum).…”
Section: Introductionmentioning
confidence: 99%
“…Sousounis and Kafali (2010) have used the AIR model in a recent study to estimate the potential cost of the 1959 typhoon in Japan. Some models use a probabilistic approach, like Gaslikova et al (2011), for the consideration of future storm surge impact in the North Sea region. The approach of Czajkowski et al (2013) presents a methodology to determine premiums on the basis of property exposure to coastal flood risk.…”
Section: Introductionmentioning
confidence: 99%